The Importance of the Occlusal Plane in Predicting Better Facial Soft Tissue in Class II Malocclusion in Ethnic Javanese - Ardani, I. Gusti Aju Wahju; Dinata, Floretta Charlene; Triwardhani, Ari (European Journal of Dentistry, 2020)
Objectives Class II malocclusion is largely due to a retrognathic mandible. Mandibular rotation is closely related to changes in the occlusal plane during growth. The problems in the occlusal plane could cause disadvantages in the soft tissue profile in Class II malocclusion, presenting treatment challenges for an orthodontist. This study aimed to investigate the importance of the occlusal plane for a better soft tissue profile in Class II malocclusion for Javanese patients.Materials and Methods The total number of cephalogram softcopies of patients with skeletal Class II malocclusion were selected based on ANB values (> 4 degrees), no agenesis teeth except the third molar, and all permanent teeth. The cephalograms were calculated using digital tracing by Morpheus 3D imaging. The points and areas to be analyzed on the cephalogram were predetermined. The examination was performed in a span of 1 month and performed via a statistical test using Pearson’s test and multiple regression analysis (p < 0.05).Results There were significant correlation values between the angles produced by the occlusal plane to sella national, Frankfurt horizontal, mandibular plane, and Z-angle (p < 0.05).Conclusion Patients with skeletal Class II malocclusion have a significant correlation between the occlusal plane and the vertical plane, thereby affecting the shape of the soft tissue profile, which causes a facial imbalance. By improving mandibular movement, the soft tissue profile can also be corrected.
Keywords: skeletal Class II malocclusion; occlusal plane; soft tissue; facial profile; cephalometric